2006
DOI: 10.1136/emj.2006.035980
|View full text |Cite
|
Sign up to set email alerts
|

Use of the emergency department by Polish migrant workers

Abstract: Following the accession of Poland to the European Union in 2004, large numbers of Polish migrant workers have come to the UK. We describe how this migration has impacted on an emergency department in the West Midlands, and suggest advice that should be given to such visitors about how to use the NHS.O n 1 May 2004 10 new countries, including the Republic of Poland, joined the European Union (EU). This allowed the free movement to the UK of workers from these countries. Soon after this date it was noticed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 2 publications
1
36
0
Order By: Relevance
“…Firstly there are likely to be more people (who are not registered with a GP (for example transients and recent migrants) and who may be unaware that they can access primary care as a temporary resident. For example, in a study of a sample of Eastern European ED attenders (carried out in the same region in which our study was set) it was found that 43% were unregistered, compared to a rate of 7.4% observed in all attenders [27]. There is also evidence that people of lower socio-economic status are less likely to be satisfied with the quality of primary care available to them [28] and that more deprived people have different expectations of primary care including a lower willingness to travel to access it [29].…”
Section: Discussionmentioning
confidence: 72%
“…Firstly there are likely to be more people (who are not registered with a GP (for example transients and recent migrants) and who may be unaware that they can access primary care as a temporary resident. For example, in a study of a sample of Eastern European ED attenders (carried out in the same region in which our study was set) it was found that 43% were unregistered, compared to a rate of 7.4% observed in all attenders [27]. There is also evidence that people of lower socio-economic status are less likely to be satisfied with the quality of primary care available to them [28] and that more deprived people have different expectations of primary care including a lower willingness to travel to access it [29].…”
Section: Discussionmentioning
confidence: 72%
“…It is further recognised that recent migration of different ethnic groups may increase communication problems and therefore pose a greater need for further or different provision of AEHI 18. We believe that more studies are needed to establish how best to provide AEHI as non-written audiovisual media to families with particular language needs, while also considering their access to various forms of media.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the comprehension of discharge information is dependent upon literacy and that understanding instructions sufficiently is key to participating in one's own care 13 14 17 18. Patients with poor language skills and low literacy scores are less likely to comprehend discharge instructions13 18 and poor comprehension is a major factor in compliance 17. Language barrier significantly influences both the provision of all care in the ED19 and patient satisfaction 13…”
Section: Discussionmentioning
confidence: 99%
“…Four of these were from the programme of work relating to risktaking sexual behaviour among Eastern European men [22][23][24][25]. Of the remaining nine publications, five focused on maternal health [26][27][28][29][30], two related to primary care [31,32], one was a study on the health of Eastern European children [33], while one study examined ED use among Polish migrant workers [34]. We did not focus on the type of study or intervention so this information was not charted.…”
Section: Chartingmentioning
confidence: 99%